2011
DOI: 10.1038/nutd.2011.8
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic activity of gut microbiota in obese children is increased compared with normal-weight children and exhibits more exhaustive substrate utilization

Abstract: Objective:The gut microbiota contribute otherwise impossible metabolic functions to the human host. Shifts in the relative proportions of gut microbial communities in adults have been correlated with intestinal disease and have been associated with obesity. The aim of this study was to elucidate differences in gut microbial compositions and metabolite concentrations of obese versus normal-weight children.Materials and methods:Fecal samples were obtained from obese (n=15; mean body mass index (BMI) s.d. score=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 46 publications
6
124
2
2
Order By: Relevance
“…A recent meta-analysis concluded that there were no statistically significant differences across multiple studies in the Firmicutes/Bacteroidetes ratio between obese and normal-weight adults (Walters et al, 2014). In agreement with this meta-analysis, some pediatric studies have Ismail et al, 2011;Payne et al, 2011). Although in our study the Firmicutes/Bacteroidetes ratio was significantly elevated in obese individuals, we observed large variation in the ratio, particularly within the obese group.…”
Section: Discussioncontrasting
confidence: 40%
“…A recent meta-analysis concluded that there were no statistically significant differences across multiple studies in the Firmicutes/Bacteroidetes ratio between obese and normal-weight adults (Walters et al, 2014). In agreement with this meta-analysis, some pediatric studies have Ismail et al, 2011;Payne et al, 2011). Although in our study the Firmicutes/Bacteroidetes ratio was significantly elevated in obese individuals, we observed large variation in the ratio, particularly within the obese group.…”
Section: Discussioncontrasting
confidence: 40%
“…Later on, 20 mM of each SCFA or mixed SCFAs (similar to concentration in the colon) (Cummings et al, 1987;Kiefer et al, 2006;Treem et al, 1994) were used in the entire study. The mixture proportion of SCFAs was 3:1:1 ratio of acetate, propionate and butyrate, respectively (Payne et al, 2011;Hijova & Chmelarova, 2007). The cells then were incubated at 37 C in a humidified 5% CO 2 atmosphere for 72 h or until confluence.…”
Section: Cells Co-culture and Stimulationmentioning
confidence: 99%
“…Finally, given the fact that gut microbiota both yield energy for their own growth and produce end products such as short chain fatty acids (SCFAs) for host metabolism (17) suggests that metabolomics are also required to understand the relationship between gut microbiome, obesity, and metabolic dysfunction. The metabolic activity of the gut microbiota is increased in obese children compared with lean children, thus gut dysbiosis is not limited to obesity in adulthood; it has also involved in the etiology of childhood obesity (18). As in the adult literature, there is evidence to suggest that not only are there shifts in fecal microbial populations in overweight children, but also variations in bacteria exist at the species levels (19).…”
mentioning
confidence: 71%